<span>Simplifying
3x + 6 = 2x
Reorder the terms:
6 + 3x = 2x
Solving
6 + 3x = 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
6 + 3x + -2x = 2x + -2x
Combine like terms: 3x + -2x = 1x
6 + 1x = 2x + -2x
Combine like terms: 2x + -2x = 0
6 + 1x = 0
Add '-6' to each side of the equation.
6 + -6 + 1x = 0 + -6
Combine like terms: 6 + -6 = 0
0 + 1x = 0 + -6
1x = 0 + -6
Combine like terms: 0 + -6 = -6
1x = -6
Divide each side by '1'.
x = -6
Simplifying
x = -6
</span>so the answer is x =-6
According to http://www.geteasysolution.com/3x+6=2x
Answer:
8.75h = 50
Step-by-step explanation:
h is the number of hours Thomas needs to groom the dogs.
The rate is $8.75 per hour.
His goal is $50.
$8.75 × h = $50
$8.75h = $50
The answer would be (x+1)(x+3)